Problematika Hukum atas Pembentukan Perubahan Kedua atas UU KPK - Sardjana Orba Manullang; Yessy Kusumadewi; Verawati Verawati; Henry Kristian Siburian; Hendro Siburian; Baren Sipayung (Journal on Education, 2023)
This research is motivated by the rampant cases of corruption that occur in Indonesia. In this research, it aims to find novelty from previous research related to the formation and legal impact of the implementation of the 2nd revision of the KPK Law. The results of the study show that the birth of the Corruption Eradication Commission Law is a legal political embodiment of bureaucratic reform in eradicating KKN in government agencies. KPK as a law enforcement agency should not need to be dichotomized and included in a partial branch of power because of its independent function. The transition of employment status from KPK Employees to ASNs who have to go through the TWK stages which do not have objective standards resulting in the dismissal of some KPK employees is a form of constitutional loss due to the second amendment to the KPK Law. Thus, the dismissed KPK employee in order to restore his constitutional rights can submit a judicial review of the second amendment to the KPK Law to the Constitutional Court as a form of public participation in the field of oversight.